Pengaruh Profitabilitas, Likuiditas dan Total Asset Turnover Terhadap Struktur Modal Pada Perusahaan Sub Sektor Kosmetik Dan Barang Keperluan Rumah Tangga Yang Terdaftar Di Bursa Efek Indonesia - Yusra, Muhammad .; Yunita, Nur Afni; Putri, Rani Gesta (Jurnal Visioner & Strategis, 2024)
This research aims to examine the effect of profitability, liquidity and total asset turnover on the capital structure of cosmetics and household goods companies listed on the Indonesia Stock Exchange (BEI) in 2018 - 2022. The population in this study is cosmetics and household goods companies. namely as many as 6 companies. The sampling technique in this research uses saturated sampling, where the entire population is sampled. The data used in this research is secondary data and comes from the official website www.idx.co.id. This research used 6 samples with 5 years of research for a total of 30 companies with multiple linear regression estimates of panel data processed using the Eviews 12 application. The results of this research using a partial test (t test) found that the profitability variable had a negative and insignificant effect on structure. capital, liquidity have a negative and significant effect on capital structure and total asset turnover has a positive and significant effect on capital structure. Keywords: Profitability, Liquidity, Total Asset Turnover, Capital Structure